6 - Les petites Suzette aux colonies. La Semaine de Suzette et la culture coloniale pendant l’entre-deux-guerres - Alain Tirefort, (Afrika Zamani, 2022)
La Semaine de Suzette, a weekly magazine for girls, first appeared in 1905. Buil- ding its success on the quality of its texts, its varied columns and iconographies, La Semaine de Suzette owes, among other things, its fame to the adventures of Bécas- sine, the young Breton girl drawn by Joseph Pinchon based on a story by Caumery. As the texbooks modelled the spirit of the Third Republic French school pupils, by diffusing a patriotic and colonial message, the youth literature takes part in its own way in consolidating the colonial imaginaire. It is thus interesting to understand how this well illustrated ‘lovely’, middle-class and catholic newspaper’ has worked to anchor in young sensibilities the conscience of ‘Great France’. More particularly, how the representations of the Africans and Asian were conveyed to a young girl audience. Does La Semaine de Suzette—1905–1960—reflect an ideology based on the conviction of the European superiority? Does it make its readers dream of ‘exotic adventures and imperial possession’? Does it generate discourse—texts and images—dentical to those, produced at the same time by the male child press?